(untitled) (Research, Society and Development, 2024)
This article addresses Celiac Disease (CD), an autoimmune disorder triggered by ingesting gluten, a protein found in wheat and other cereals. This study aimed to raise awareness among health professionals and people with celiac disease about the importance of nutrition and strict adherence to a gluten-free diet, exploring the relationship of celiac patients with food through the analysis of scientific articles on the subject. The CD is characterized by an abnormal immune response that damages the intestinal mucosa, affecting the absorption of nutrients and resulting in several gastrointestinal and extraintestinal symptoms, such as anemia and osteoporosis. Treatment requires a strict gluten-free diet, and adequate food labeling is essential. This study aims to raise awareness among celiac patients about the importance of nutrition and adherence to a gluten-free diet by analyzing relevant scientific articles.